Transgenic bovine as bioreactors: Challenges and perspectives. Issue 3 (1st April 2016) - Monzani, Paulo S.; Adona, Paulo R.; Ohashi, Otávio M.; Meirelles, Flávio V.; Wheeler, Matthew B.
ABSTRACT: The use of recombinant proteins has increased in diverse commercial sectors. Various systems for protein production have been used for the optimization of production and functional protein expression. The mammary gland is considered to be a very interesting system for the production of recombinant proteins due to its high level of expression and its ability to perform post-translational modifications. Cows produce large quantities of milk over a long period of lactation, and therefore this species is an important candidate for recombinant protein expression in milk. However, transgenic cows are more difficult to generate due to the inefficiency of transgenic methodologies, the long periods for transgene detection, recombinant protein expression and the fact that only a single calf is obtained at the end of each pregnancy. An increase in efficiency for transgenic methodologies for cattle is a big challenge to overcome. Promising methodologies have been proposed that can help to overcome this obstacle, enabling the use of transgenic cattle as bioreactors for protein production in milk for industry.